Islamic Banking and Empowerment of Small Medium Enterprise - Femei Purnamasari; Arif Darmawan (Faculty of Economic and Business, 2017)
This study explores the effectiveness of developing SMEs with role of Islamic Banking in Indonesia. The study also want to prove the role of Islamic banking to help SMEs in Indonesia based on data and research. Data analysis and methods that used in this study is descriptive statistical methods. Descriptive statistics will elaborate with some explanation data and can be figured by frequency distribution and center of distribution data. The result shows that development of SMEs regarding both the number of business units, employment, and financing from Islamic banking indicates a positive direction or increased significantly. In addition, the interaction between SMEs and Islamic banking is quite close relatively but need to be upgraded. The study only gives general overview and description about positive impact from Islamic banking mechanism to stimulate SMEs in Indonesia. The data and result provided still need to be discussed with more comprehensive literature and fact study on the ground.DOI:10.15408/etk.v16i2.5355